-13+9=m-7

Simple and best practice solution for -13+9=m-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13+9=m-7 equation:


Simplifying
-13 + 9 = m + -7

Combine like terms: -13 + 9 = -4
-4 = m + -7

Reorder the terms:
-4 = -7 + m

Solving
-4 = -7 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-4 + -1m = -7 + m + -1m

Combine like terms: m + -1m = 0
-4 + -1m = -7 + 0
-4 + -1m = -7

Add '4' to each side of the equation.
-4 + 4 + -1m = -7 + 4

Combine like terms: -4 + 4 = 0
0 + -1m = -7 + 4
-1m = -7 + 4

Combine like terms: -7 + 4 = -3
-1m = -3

Divide each side by '-1'.
m = 3

Simplifying
m = 3

See similar equations:

| -73+13x=165+6x | | 6+3m-3=9m+12-7m | | x-9=-4+6 | | 3x-220=80+13x | | 2n=25+12 | | 1/9x+4=13 | | 90=7x+2(x-9) | | =20x | | -7-k=-(-8k-4)-2 | | 9y-15=4y-10 | | 3(2y+5)-8y=1 | | -5v-(1-7v)=15 | | 0=3y+42-9y | | X+91/4=127/16 | | 0=3gy+42-9y | | 8*2-9*9+9= | | 51/4+31/2 | | 56x^2+x-72=0 | | 0=-6x-5(-3x+9) | | 9+k=17 | | 8-5v-3=5v-5 | | 84=-16t+72t+3 | | -62-13x=136-4x | | s^2-4s=12 | | 3k+4/7 | | 2x-7+5/x=0 | | -5+(-16)=4x-7x | | 14x^2-60x+26=0 | | 5x+8y= | | 93=27x | | 7x^2-30x+13=0 | | 1-16n^2=0 |

Equations solver categories